Analisis I’jaz Lughawy dalam Surah Al-Ikhlas: Telaah Keindahan Struktur Bahasa Al-Qur’an - Ahya Dita Satiarmia L; Jauhar Hatta; Nasiruddin; Mufidah Asri Azizah; Azmalia Anastasya Marcella (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
This study examines the linguistic miracle in Surah Al-Ikhlas, focusing on the linguistic structure and rhetorical devices that form its linguistic miracle. Unlike previous studies, which generally emphasize theological dimensions and thematic interpretations, this study affirms its contribution by combining modern linguistic analysis and classical balāghah theory to read Surah Al-Ikhlas more systematically. This study uses a qualitative descriptive approach through textual analysis of diction choices, phonetic rhythm, and rhetorical devices such as ījāz, ṭibāq, and taqdīm–ta’khīr, supported by classical and contemporary exegetical references. The results show that Surah Al-Ikhlas has a very concise yet precise, harmonious, and richly meaningful linguistic construction, thus confirming the i'jāz lughawī character that is the main feature of the miraculous nature of the Qur'an. These findings show that the power of the message of tawhid in Surah Al-Ikhlas lies not only in its meaning but also in its structured and effective linguistic design.